Dimensionality Effects in Anisotropic Single Layers TiSe5 and TiTe5: a Comparative Study of 2D Sheets and 1D Nanochains - Yağmurcukardeş, Mehmet; Can Dogan, Kadir; Kutay Tamdogan, Omer; Bozkurt, Yagmur; Cetin, Zebih; Yagmurcukardes, Mehmet (IOP Publishing Ltd, 2026)
In this study, we present a comprehensive first-principles investigation of the structural, vibrational, and electronic properties of titanium pentachalcogenide structures in both two-dimensional (2D) and one-dimensional (1D) nanochain (NC) forms. Total energy and geometry optimizations reveal that the 2D TiX5 (X = Se, Te) structures exhibit in-plane anisotropy arising from the trigonal prismatic TiX3 units interconnected via the chalcogenide chains. Phonon band dispersions and elastic tensor elements confirm the dynamical and mechanical stability of the 2D layers, respectively. Electronically, while TiTe5 is a metal, TiSe5 possesses direct band gap semiconducting behavior. In addition, free-standing 1D NC counterparts, which are sub-units of the 2D structures, are investigated by means of their stability. Three stable 1D NCs, namely TiTe5-NC, TiSe7-NC, and TiTe7-NC, are found to be composed of edge-sharing TiX6-like units with either five- or seven-fold coordination. The dynamically stable 1D NCs are shown to be semiconductors with relatively larger band gaps as compared to 2D layers. Predicted Raman spectra reveal clear signatures of vibrational mode evaluations as a result of quantum confinement from the 2D layer to the 1D NC. Moreover, finite-temperature ab-initio quantum molecular dynamics simulations at 300 K confirm the thermal stability of both the 2D TiX5 layers and 1D NC derivatives, showing that the Ti-based systems retain their structural integrity under ambient conditions and are feasible candidates for experimental synthesis. Our findings highlight the formation of stable semiconducting 1D NCs of Ti-pentachalcogenides from their 2D counterparts.
Yagmurcukardes, Mehmet/0000-0002-1416-7990; Bozkurt, Yağmur/0000-0002-1192-1249; Çetin, Zebih/0000-0002-2858-7144; Doğan, Kadir Can/0000-0001-8497-2402
Keywords: Density Functional Theory; Low-Dimensional Materials; Titanium Pentachalcogenides; Dimensionality Effects; Raman Theory